Kajian Sastra Perbandingan Puisi Kangen Karya Ws.Rendra dengan Puisi Kangen di Malam Sunyi Karya Li Bai (International Forum of Researchers and Lecturers, 2024)
The aim of this research is to examine the differences in Indonesian poetry entitled Kangen by Ws. Rendra with a Chinese poem entitled Missing You in the Silent Night by Li Bai. Poetry is a form of literary work alongside prose and drama. Compared to other forms of literary work, poetry has a unique character, namely that it uses words that are considered to represent certain meanings, is dense, dominated by symbols, and has limited space. Comparative literature is the activity of comparing the literature of one country with the literature of another country or comparing literature with other fields as an overall expression of life (Endraswara, 2011:10). One of the poems known in Indonesian literature is the poem entitled